Symmergent Gravity, Seesawic New Physics, and Their Experimental Signatures - Durmuş Demir (Advances in High Energy Physics)
The standard model of elementary particles (SM) suffers from various problems, such as power-law ultraviolet (UV) sensitivity, exclusion of general relativity (GR), and absence of a dark matter candidate. The LHC experiments, according to which the TeV domain appears to be empty of new particles, started sidelining TeV-scale SUSY and other known cures of the UV sensitivity. In search for a remedy, in this work, it is revealed that affine curvature can emerge in a way restoring gauge symmetries explicitly broken by the UV cutoff. This emergent curvature cures the UV sensitivity and incorporates GR as symmetry-restoring emergent gravity (symmergent gravity, in brief) if a new physics sector (NP) exists to generate the Planck scale and if SM+NP is Fermi-Bose balanced. This setup, carrying fingerprints of trans-Planckian SUSY, predicts that gravity is Einstein (no higher-curvature terms), cosmic/gamma rays can originate from heavy NP scalars, and the UV cutoff might take right value to suppress the cosmological constant (alleviating fine-tuning with SUSY). The NP does not have to couple to the SM. In fact, NP-SM coupling can take any value from zero to ΛSM2/ΛNP2 if the SM is not to jump from ΛSM≈500  GeV to the NP scale ΛNP. The zero coupling, certifying an undetectable NP, agrees with all the collider and dark matter bounds at present. The seesawic bound ΛSM2/ΛNP2, directly verifiable at colliders, implies that (i) dark matter must have a mass ≲ΛSM, (ii) Higgs-curvature coupling must be ≈1.3%, (iii) the SM RGEs must remain nearly as in the SM, and (iv) right-handed neutrinos must have a mass ≲1000  TeV. These signatures serve as a concise testbed for symmergence.